Uji Efek Analgetik Infusa Daun Beluntas (Pluchea indica L.) Pada Mencit Jantan Galur Swiss - Sri S. Wahyuningsih; Linda Widyastuti (Jurusan Biologi FMIPA Universitas Cenderawasih, 2015)
Beluntas leaves (Pluchea indica L.) have been known as analgetic reducer. The study about this research has been going on right now. The goal of this research is to study the analgesic effect of beluntas (P. indica) leaf infused into male mice of swiss strain. The method used is the stretching chemical stimuli using acetic acid as an inducer of pain. Healthy male mice of Swiss strain were divided into five groups, and each group consisted of 5 mice. Group I was given paracetamol at a dose of 65 mg/kg of body weight, group II were given distilled water , the group III-V were given beluntas leaf infuse in the variation of 10 %, 20 % and 40 %. Thirty minutes after test substance application, acetic acid of 100 mg/kg of body weight were given intraperitoneally in all groups and stretching of mice was observed every 5 minutes for 1 hour. The data was analyzed by using normality test of Kolmogorov-Smirnov; the test of homogeneity of variance was analyzed by ANOVA and post hoc tests were to differenciate the percentage analgetic of every group. Statistical test showed normal distributed and homogeneous data; there are significant differences of percentage analgesic between paracetamol and beluntas leaf infuse of 10, 20, and 40 % (p < 0.05). There was significant differences between infuse of beluntas leaves with positive control (parasetamol) in mice. Key words: Analgetic, leave of beluntas (P. indica), infuse, mice.